Adjusting ventilator settings to avoid air trapping in extremely premature infants reduces the need for tracheostomy and length of stay - Sammour, Ibrahim; Conlon, Steven M.; Bauer, Sarah E.; Montgomery, Gregory S.; Cristea, A. Ioana; Rose, Rebecca S. (Frontiers in Pediatrics, 2022)
Despite the improving understanding of how lung mechanics and tidal volume requirements evolve during the evolution of bronchopulmonary dysplasia (BPD), clinical management continues to be heterogeneous and inconsistent at many institutions. Recent reports have examined the use of high tidal-volume low respiratory rate strategies in these patients once disease has been well established to help facilitate their eventual extubation and improve their long-term neurodevelopmental outcomes. In this retrospective observational research study, we describe how intentional adjustment of ventilator settings based on patient lung mechanics by an interdisciplinary BPD team improved the care of the at-risk population of infants, reduced the need for tracheostomies, as well as length of stay over a period of over 3 years. The team aimed to establish consistency in the management of these children using a high tidal volume, low-rate approach, and titrating PEEP to address the autoPEEP and bronchomalacia that is frequently observed in this patient population.